Experiences, coping strategies and perspectives of people in Malaysia during the COVID-19 pandemic - Phaik Kin Cheah; Mohamed Bella Jalloh; Phee-Kheng Cheah; Darlene Ongkili; Mira Leonie Schneiders; Anne Osterrieder; Pimnara Peerawaranun; Naomi Waithira; Alun Davies; Mavuto Mukaka; Phaik Yeong Cheah (BMC, 2023)
Abstract Background A nationwide Movement Control Order (MCO) was enforced in Malaysia on 18 March 2020 in view of the global COVID-19 pandemic. Malaysia implemented various public health measures and later raced against time to administer COVID-19 vaccines when they became available. As a result of various public health measures to curb the spread of the virus, people in Malaysia faced unprecedented circumstances and new challenges. This study addressed the knowledge gap in our understanding the experiences, coping strategies and perspectives of the people in Malaysia about infection countermeasures by investigating their experiences during the COVID-19 pandemic. Methods A sequential mixed method approach was used to conduct an online survey and in-depth interviews among residents in Malaysia. A total of 827 respondents participated in the online survey from 1st May to 30th June 2020. Nineteen in-depth interviews were conducted online and by phone with key informants and members of the public, who were selected through maximum variation purposive sampling between 2nd May 2020 to 20th December 2021. The semi-structured interviews employed a phenomenological approach and transcripts were analysed using thematic analysis. The survey data were analysed using descriptive statistics in Stata 15.0. Results The survey reflected significant economic impacts of the pandemic, the maximum number of days that people could cope during the MCO, and their coping strategies, which generally entailed changes in lifestyle. The internet and social media were vital platforms to mitigate against the impact of public health measures. Thematic analysis of the interview data revealed participant experiences and perceptions of COVID-19 and public health measures in four main themes: (1) work and business; (2) emotional impact (3) coping with change and (4) the COVID-19 vaccine. Conclusions This study provides insights into the experiences, coping strategies and perspectives of people in Malaysia living through the first-ever MCO during the COVID-19 pandemic. Such insights into COVID-19-related public health measures are pertinent for successfully planning and implementing future responses to pandemics.